Pengaruh Perebusan Telur Ayam Kampung Terhadap Kadar Protein - Khaerati, Khildah (Media Eksakta, 2011)
The aim of this research was to compareÂ  the protein content ofÂ  â€œ kampungâ€ chickenâ€™s eggÂ  before and after poaching. Qualitative analysis was done using Biuret, Millonâ€™s, and Ninhydrin reagents, producing violet, red, and blue-violet, respectively. Quantitative analysis was done by the Kjeldahl method. The resulf of the investigation showed that length of poaching time influenced the protein content of â€œkampung" chicken eggs. The protein content before the poaching treatment was 12,84 %, after 3 minutes of poaching 12,33 %, after 6 minutes 11,35 %, and after 12 minutes 10,95 %. Using statisticalanalysis, those data prored to be significantly different.